Physical and Chemical Characteristics of Lake Edku Water, Egypt - OKBAH, M.A.; EL-GOHARY, S.EL. (Mediterranean Marine Science, 2002)
The objective of this work is to evaluate the quality of Lake Edku water. Regional and seasonal variations of some physico-chemical parameters (nutrient salts, total nitrogen, total phosphorous and silicate, in addition to pH, total alkalinity, chlorosity, dissolved oxygen, biological oxygen demand and oxidizable organic matter) that were determined during the period from January to December 2000. Important variations have occurred in the investigated area as a result of human activity and the discharge of wastewater to the lake. The relatively low pH values reflect the decreased productivity of the Lake as a result of the polluted water discharged into the lake. Total alkalinity varied between 2.25 ± 0.35 to 8.38 ± 0.9 meq/l. In comparison with previous decades chlorosity content (586-1562 mg/l) showed the general decreasing trend. Dissolved oxygen varied (2.37 ± 0.72 - 4.47 ± 0.94 mg/l). The ratios of BOD/ OOM values indicate that the lake water has a biodegradable nature. There was a noticeable variation in ammonia levels; a lower ammonia content was recorded in summer and spring. Nitrite and nitrate concentrations in Lake Edku water showed values ranging from 3.7±1.4 to 7.8±1.9 ΜM and from 15.2±2.9 to 45.9±11.8 ΜM, respectively. The total nitrogen of the lake exhibited higher levels (53.1±12.2 – 164.2±30.7 ΜM). The ratio of NH4/TIN (0.09-0.45) seems to be highly representative of the microbial nitrification rate as well as of the varying agricultural inflows. It is interesting to note that increasing values of reactive phosphate (11.6±1.8 – 14.7±2.5 ΜM) were determined in autumn and winter respectively. The higher concentrations of reactive silicate were directly proportional to drainage water discharged into the Lake. It is clear from the mean ratio of N/P (2.4-8.8) nitrogen is the limiting factor. The lower values of N/P ratio could be related to an allochthonous condition.